2016
DOI: 10.18632/oncotarget.8862
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative ultrasound assessment of breast tumor response to chemotherapy using a multi-parameter approach

Abstract: PurposeThis study demonstrated the ability of quantitative ultrasound (QUS) parameters in providing an early prediction of tumor response to neoadjuvant chemotherapy (NAC) in patients with locally advanced breast cancer (LABC).MethodsUsing a 6-MHz array transducer, ultrasound radiofrequency (RF) data were collected from 58 LABC patients prior to NAC treatment and at weeks 1, 4, and 8 of their treatment, and prior to surgery. QUS parameters including midband fit (MBF), spectral slope (SS), spectral intercept (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
(51 reference statements)
3
43
0
Order By: Relevance
“…To compute the US and PA spectral parameters as a function of time post-treatment, the average, normalized power spectrum (PS norm ) was computed by removing the system dependencies through the use of the reference phantom technique developed for QUS [9]:PSnormUS(f,z)=1Si=1Slog10(Ufalse(f,zifalse)tumorUfalse(f,zifalse)ref)2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compute the US and PA spectral parameters as a function of time post-treatment, the average, normalized power spectrum (PS norm ) was computed by removing the system dependencies through the use of the reference phantom technique developed for QUS [9]:PSnormUS(f,z)=1Si=1Slog10(Ufalse(f,zifalse)tumorUfalse(f,zifalse)ref)2…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative ultrasound (QUS) [6], [7], [8], [9], [10] and Diffuse Optical Spectroscopy Imaging (DOSI) [11], [12], [13], [14], [15] are two promising modalities in early cancer treatment monitoring. QUS utilizes the frequency content of the ultrasound radiofrequency (US RF) signals to extract relevant information about the changes in the structural properties of cancer tumor tissue during treatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the mean of intensity of ASD and AAC images derived from US backscatter are effective in a similar clinical application. Furthermore, Tadayyon et al 23. demonstrated that a QUS multi-parametric imaging approach utilizing MBF, SS, and mean scatterer spacing parameters submitted to a k-nearest neighbor (k-NN) classifier is an effective method of predicting breast tumour responses to chemotherapy early during the course of the treatment.…”
mentioning
confidence: 99%
“…Sannachi et al 22,. and Tadayyon et al 23. with the following key contributions:

Baseline QUS imaging features were evaluated in terms of their ability to predict breast tumour response in advance of any treatment.

In addition to examining textural features within the tumor core as done previously, QUS features in the tumor’s surrounding tissue, referred to here as the margin, extending 3–10 mm from the core were analyzed.

…”
mentioning
confidence: 99%
See 1 more Smart Citation